If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -1(4x + 5) = 0 Reorder the terms: 6x + -1(5 + 4x) = 0 6x + (5 * -1 + 4x * -1) = 0 6x + (-5 + -4x) = 0 Reorder the terms: -5 + 6x + -4x = 0 Combine like terms: 6x + -4x = 2x -5 + 2x = 0 Solving -5 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 2x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 2x = 0 + 5 2x = 0 + 5 Combine like terms: 0 + 5 = 5 2x = 5 Divide each side by '2'. x = 2.5 Simplifying x = 2.5
| 6(3x-2)= | | 5(c-4)+2c=3(c+10)-2 | | 3x^2+2+4x=0 | | -2+7x+7x=138 | | x^2=13x-40 | | -x+5+7x=17 | | 1+x+5x=55 | | 24a^4b^2= | | n^2-4n-60=0 | | 0.45x+0.05(4-x)=0.10(58) | | 6-3x=0 | | A^2-5=-4a | | x+6+x=10 | | 2g^2-4g=20 | | -0.10(5)+0.25x=0.05(x-2) | | 9-3+2=10 | | 3x^2-7x+1= | | -4-x+6x=16 | | 2.3q-16=5q+36 | | 0.18y+0.02(y+8000)=1360 | | -5x-4-5x=16 | | 1.5+1.5n=21 | | -3(z-8)=6 | | x=4x-12 | | x=4x-2 | | 8+4x+4x=72 | | 2x-(-7)=3(x+10) | | 24x^2+47x+k=0 | | (3m+8)(5m-3)= | | -8.6-3z-8.5-z=-3z+2.3 | | 2(1-x)=3(x+9) | | n+12=n*4 |